The Impact of Health Education Counseling on Rate of Recurrent Sexually Transmitted Infections in Adolescents - Supinya In-iw (2018)
© 2015 North American Society for Pediatric and Adolescent Gynecology. Study Objective: To evaluate the effectiveness of a sexually transmitted infection (STI) intervention by a health educator that included partner notification, condom use, and retesting within 3 months.Design, Setting, and Participants: Retrospective chart review was conducted, and data were collected from 274 sexually active adolescent girls, aged 15 to 19 years, who were diagnosed with gonorrhea (GC), Chlamydia (CT), and Trichomonas (TV) infection, during a 9-month span in an urban hospital-based adolescent medicine clinic.Methods: Data regarding recurrent STIs (GC, CT, and TV) were collected for 12 months following the incident infection. There were 161 in the intervention group (health educator counseling), and 113 controls who received usual care. Differences between groups were analyzed using χ2and survival analyses.Results: There were no significant differences in age, gender, or race between the intervention and control groups at baseline. The majority in both groups were diagnosed initially with CT infection (57% CT, 16% GC, and 5% TV in the intervention group; 46% CT, 21% GC, and 12% TV in the control group). There was a significantly lower rate of STI in the intervention group for those retested within 12 months of the initial diagnosis (P = .002). The median (SD) time to recurrence in the intervention group was greater: 134 (14.7) days versus 116 (12.1) days (P = .034). Health education counseling, initial diagnosis with TV, and duration of time from initial diagnosis to retest (interval to retest) were significant protective factors for recurrent STI.Conclusions: Health education counseling in an urban adolescent clinic is effective in reducing recurrent infection at 12-month follow-up and can serve as an important component in reducing STI recidivism.